Alarm Pengendali Asap Pada Ruangan Bebas Asap Berbasis Mikrokontroler Arduino - Winarno Fadjar Bastari; Akhmad Solikin; Widodo Widodo (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2022)
Smoke is air pollution that is very dangerous for human health. Therefore, in this study the authors designed and modeled a fan speed controller using a smoke sensor based on an Arduino microcontroller. In addition, smoke control alarms can also be used for monitoring in smoke-free rooms in order to prevent and at the same time provide a deterrent effect on people who smoke in places where smoking is prohibited. The method used is to process the data detected by the MQ2 smoke sensor, then display the amount or level of smoke in the room and its condition on the LCD/monitor. The comparison of the values on the sensor will be processed with the Arduino and the output of the Arduino will be input coding on the Arduino IDE software to control the fan speed performance as a response to exhaust air in the ventilation area of the room. The microcontroller process is in the program as a controller of all components, then coding will control all components according to the coding ordered in the microcontroller and voltage controller at the smoke sensor input and LCD and fan output. The results obtained from this research project are able to detect the state of the air in a smoke-free room from smoke and CO pollution from 0 ppm to = 256 ppm and this pollution can be reduced by adjusting the fan speed as room air ventilation to avoid the deposition of smoke in a smoke-free room. which is dangerous. So that the air in the room becomes cleaner and safer for health.